186. RECURRENT DISEASE AFTER ESOPHAGEAL CANCER SURGERY; A SUBSTUDY OF THE DUTCH NATIONWIDE IVORY STUDY. (24th September 2022) - Henckens, Sofie; Kalff, Marianne; Voeten, Daan; Heineman, David; Hulshof, Maarten; van Laarhoven, Hanneke; Eshuis, Wietse; Baas, Peter; Bahadoer, Renu; Belt, Eric; Brattinga, Baukje; Claassen, Linda; et al.
Abstract: Survival of recurrent esophageal cancer is usually poor, with limited prospects of remission. This study investigated the predictors, patterns and survival of recurrent disease following esophageal cancer surgery. This nationwide cohort study included patients with resectable distal esophageal and gastroesophageal junction adenocarcinoma and squamous cell carcinoma undergoing curatively intended esophagectomy from January 2007 until December 2016 (follow-up until January 2020). Patients with distant metastases detected during surgery were excluded. Univariable and multivariable logistic regression were used to identify predictors of recurrent disease. Multivariable Cox regression was used to determine the association of recurrence site (locoregional or distant) and treatment intent (none, palliative, curative) with post-recurrence survival. Among 4626 patients, 45.1% developed recurrent disease at a median of 11 months postoperatively, of whom most had distant metastases (59.8%). Disease recurrences were most frequently hepatic (26.2%) or pulmonary (25.1%). Young age (≤65 years), male sex, adenocarcinoma, open surgery, transthoracic esophagectomy, non-radical resection, higher T-stage, and (y)pN+ stage were significantly associated with disease recurrence. Overall, median post-recurrence survival was 4 months (95%CI 3.6–4.4). Median survival after locoregional recurrence was 7 months (95%CI 5.7–8.4) and favorable compared to distant recurrence (HR = 0.74, 95%CI 0.65–0.84). For 127 patients that underwent curatively intended treatment for recurrence, median survival was 20 months (95%CI 16.4–23.7). This study provides important prognostic information assisting in the surveillance and counseling of patients after curatively intended esophageal cancer surgery. Nearly half of included patients developed recurrent disease, and risk of recurrence was higher in patients with, amongst others, higher tumor stage, non-radical resection and tumor positive lymph nodes. Overall, patients with recurrent disease had limited prospects of survival, although median survival after curatively intended treatment reached 20 months.